EPISTEMOLOGI PEMIKIRAN ANDREW RIPPIN DAN IMPLIKASINYA TERHADAP FUNGSI ASBABUN NUZUL (Analisis Atas Artikel The Function of Asbab An-Nuzul in Qur'anic Exegesis) - Ahmad Ghozali; Muhammad Azka Noor (Mafatih, 2022)
This article discusses the epistemology of Andrew Rippin's thought which is considered different from that of his teacher John Wansbrough. The sources of knowledge used by Rippin come from John Wansbrough, as-Suyuti, al-Wahidi, Ibn As'ad, al-'Iraki, and books at the Staatsbibliothek, Berlin. The method or approach he uses is a historical or historical horizon and literary analysis. Validity Truth is based on coherence theory, correspondence theory, and pragmatism theory. This study also shows the implications of Rippin's thoughts on the function of Asbab an-Nuzul. First, many Muslim scholars have written about Asbab an-Nuzul, but it is only a quote and then left alone. The second is a recommendation to the scholars of the Koran to reconsider the construction of Asbab an-Nuzul in its interpretation. This study is a literature review with a descriptive-analytic method of exposure to Rippin's article entitled The Function of Asbab an-Nuzul in Qur'anic Exegesis as primary data and other books as secondary data. Artikel ini membahas tentang epistemologi pemikiran Andrew Rippin yang dianggap berbeda dengan pemikiran gurunya John Wansbrough. Sumber-Sumber Pengetahuan yang digunakan Rippin bersumber dari John Wansbrough, as-Suyuti, al-Wahidi, Ibnu As’ad, al-‘Iraki, dan buku di Staatsbibliothek, Berlin. Metode atau pendekatan yang digunakannya adalah horizon historis atau sejarah dan analisis sastra. Validitas Kebenaran berdasarkan teori koherensi, teori korespodensi, teori pragmatism. Serta kajian ini juga memperlihatkan implikasi pemikiran Rippin terhadap fungsi Asbab an-Nuzul. Pertama, sarjana muslim banyak yang menulis tentang Asbab an-Nuzul namun hanya sebatas kutipan kemudian dibiarkan. Kedua menjadi rekomendasi kepada kesarjanaan Quran mempertimbangkan kembali kontruksi asbab an-nuzul dalam penafsirannya. Kajian ini merupakan kajian pustaka dengan metode pemaparan deskriptif-analitis terhadap artikelnya Rippin yang berjudul The Function of Asbab an-Nuzul in Qur'anic Exegesis sebagai data primer dan buku-buku lainnya sebagai data sekunder.